Modyfikacja metody analizy grafów - Denkowska, Sabina (Modification of Graph Analysis Method, 2007)
Graph analysis method is the commonly known procedure of independent variables selection in linear regression model. It is based on traditional attitude to the significance testing of correlation coefficients in the correlation matrix, in which multiple testing effect is ignored because the decisions of significance are taken each on α-level. Proposed modification of graph analysis method ensures the control of multiple testing effect in a correlation matrix. This modification is based on multiple testing procedures which ensure control of probability of at least one wrong rejection when the entire family of inferences is considered (FWE Family-wise Error Rate), or the control of FDR (False Discovery Rate) which is the expected proportion of erroneously rejected null hypotheses among the rejected ones.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 341-349